Triggers of Contract Breach : Contract Design, Shocks, or Institutions? - Nose, Manabu (World Bank, Washington, DC, 2014)
This paper constructs a large contract-level data set to examine factors that trigger breach of foreign investment contracts. Similar to the case of outright expropriation, political regime type is an important determinant of breach of contract. Furthermore, although investors' bargaining power becomes obsolete as contracts mature, contracts can be designed to mitigate the risk of breach of contract by involving multilateral organizations and creating buffers to absorb commodity price shocks. The paper examines the type of countries prone to contract breaches. After controlling for regional and sector fixed effects, less-democratic and resource-dependent governments are more likely to breach contracts, especially after large global shocks, notably natural disasters.